Applications of Bone Morphogenetic Protein-2: Alternative Therapies in Craniofacial Reconstruction. Issue 7 (October 2019) - Fisher, Mark; Yee, Kristen; Alba, Brandon; Tanna, Neil; Bastidas, Nicholas; Bradley, James P.
Abstract : Abstract: Large defects of the craniofacial skeleton can be exceedingly difficult to reconstruct since autologous bone grafts are limited by donor site morbidity and alloplastic implants have low biocompatibility. Bone morphogenetic proteins (BMPs) in craniofacial reconstruction have been used with mixed outcomes and complication concerns; however, results for specific indications have been promising. In alveolar clefts, cranial vault defects, mandibular defects, and rare Tessier craniofacial clefts, BMP-2 impregnated in collagen matrix was looked at as an alternative therapy for challenging cases. In cases where structural support was required, BMP-2 was used as part of a construct with bio-resorbable plates. Demineralized bone was added in certain cases. The authors described specific indications, detailed surgical techniques, and a review of the current literature regarding the use of BMP-2 in craniofacial reconstruction. BMP-2 is a viable option for craniofacial reconstruction to decrease donor-site morbidity or when alternatives are contraindicated. It is not recommended for routine use or in the oncologic setting but should currently be reserved as an alternative therapy for complex cases with limited options. Bone morphogenetic proteins are a promising, emerging option for complex craniofacial reconstruction. Future directions of BMP-2 therapies will become apparent as data from prospective randomized trials emerges.